Do judiciário do homo faber ao poder judiciário da ação: a democratização da jurisdição do século XXI em questão - Werner, Priscila Cardoso (Universidade do Vale do Rio do Sinos, 2009)
With the torn between Society and his Judiciary, the public space disappeared. This loss had a lot of consequences, like the lost of authority and legitimacy, and the construction of a bureaucratic and little efficient institution, which can be called the Homo faber’s Judiciary as a paraphrase of the Homo faber by Hannah Arendt. More than reflecting behavioral tendencies from the society itself, this entity is reinforced by certain legal practices and instruments, almost all identified with production’s logic, in what human value is dismissed. The present study identifies and discusses this Homo faber’s Judiciary, its roots, the lost of authority who accomplish it, the events what strength it and the risk it represents for a democratic and pluralistic society. As a counterpoint, it will be suggested the vision of another institution, named as Homo activo’s Judiciary Power, where the action exercised as an attitude brings back the use of the public space, the other’s perception and the collective’s care. Some
Keywords: autoridade; espaço público; poder judiciário; authority; public space; judiciary power; Ciências Sociais Aplicadas